Bangladesh and Covid-19: Reversals and resilience - Rahman, Atiya; Jahan, Nusrat; Matin, Imran; Rahman, Hossain Zillur (Institute of Development Studies, 2024)
This article was published in The IDS Bulletin [©2022 Rights managed by Institute of Development Studies] and the definite version is available at: https://doi.org/10.19088/1968-2022.125 The Article's website is at: https://bulletin.ids.ac.uk/index.php/idsbo/article/view/3167